Pemanfaatan Gedebog Pisang Menjadi Keripik Inovatif di Dusun Kebonagung, Desa Sukolelo, Kecamatan Prigen - Fiki Izzatul Afkarina; Muslehatul Fa’izeh; Nur Faizah Muzilatul Kamelia; Nurul Wasilatur Rofi’ah; Suchaina Suchaina (Journal Economic Excellence Ibnu Sina, 2025)
Banana pseudostems are an abundant agricultural by-product that has been largely underutilized. In fact, banana pseudostems contain various nutrients such as vitamins A, B, and C, dietary fiber, and tannins, which offer potential health benefits. This study aims to explore the process of transforming banana pseudostems into an innovative food product in the form of chips, while also examining their potential benefits for health, economy, and the environment. The research was conducted through a one-month community assistance program in Kebonagung Hamlet, consisting of several stages: initial observation to identify potentials and challenges, socialization activities to raise awareness of banana pseudostem utilization, training in processing techniques for making banana pseudostem chips, and product packaging. The results of the observation indicated that the community initially had no knowledge of banana pseudostems as an alternative food source. However, through socialization and training, residents gained awareness of the added value of this agricultural waste and were able to apply simple and hygienic processing methods. The resulting banana pseudostem chips demonstrated a unique flavor, crunchy texture, and good nutritional value, making them a promising healthy snack. From an economic perspective, this innovation can open up new entrepreneurial opportunities, improve household income, and expand the diversification of local food products. Environmentally, utilizing banana pseudostems for value-added products helps reduce organic waste that would otherwise go unused. Thus, the innovation of processing banana pseudostems into chips contributes not only to improving community health and welfare but also supports sustainable development through productive use of agricultural waste.